Clinical Characteristics and Survival of Patients with Malignant Ovarian Tumors in Addis Ababa, Ethiopia. (25th April 2019) - Piszczan, Swantje; Desalegn, Dawit; Petros, Hezkiel; Gurmu, Mengistu; Kroeber, Eric Sven; Addissie, Adamu; Mikolajczyk, Rafael; Ghebre, Rahel G.; Mathewos, Assefa; Thomssen, Christoph; Jemal, Ahmedin; Kantelhardt, Eva Johanna
Abstract: Background: Ovarian cancer is the third leading cause of cancer death among women in Ethiopia, with about 2, 550 diagnosed cases and 2, 000 deaths each year. The incidence and mortality rates of this disease have been increasing in Ethiopia and other parts of sub‐Saharan Africa over the past decades because of changing lifestyle and reproductive factors. In this study, we describe the clinical characteristics, treatment patterns, and survival of patients with ovarian cancer in Ethiopia. Materials and Methods: This retrospective cohort study included 485 patients diagnosed between January 2009 and October 2015 at Addis Ababa University Hospital, Zewditu Memorial Hospital, or registered in the Addis Ababa population‐based cancer registry. Follow‐up data were obtained via telephone. Primary endpoint was all‐cause mortality. Results: The median age was 46 years (range, 11–95). The estimated 1‐ and 2‐year overall survival rates were 78% (95% confidence interval [CI] 0.741–0.82.5) and 59% (95% CI, 0.538–0.646), respectively. Of those patients with result available ( n = 423), 73.0% had epithelial cancers. Almost half were classified as Federation of Gynecology and Oncology stage III or IV (48.2%; stage available n = 201) resulting in worse outcomes (hazard ratio [HR], 2.91 [CI 0.67–12.64] and 3.03 [0.69–15.79], respectively). Four out of five patients received some form of surgery (82%), three out of five received platinum‐containing chemotherapy. Patients with residual tumor after surgery ( n = 83) showed worse survival outcome (HR, 2.23; 95% CI 1.08–4.49). Conclusion: Our study revealed substantial treatment gaps with respect to surgery and adequate chemotherapy. Higher stage, residual tumor and lack of chemotherapy impaired the outcome. Access to higher standards of ovarian cancer treatment is urgently needed in Ethiopia. Abstract : The burden of ovarian cancer in Ethiopia is rising. This article evaluates clinical characteristics, treatment patterns, and outcomes in patients with ovarian malignancies in Ethiopia.